Islamic Banking Products and Economic Development in Nigeria: A Co-Integration Approach - Habeeb Olaniyi Olayiwola (Journal of Islamic Economic and Business Research, 2021)
The authorization of Taj Bank Limited to operate Islamic banking in Nigeria has reiterated the relevance of Islamic banking products and services in the nation’s economy. However, the rate of patronage has been dampened compared to the conventional banks due to the issues of regulations and taxes, issues revolving around Sharia Scholars, Sharia-compliant products, and lack of awareness, among others. The study, therefore, investigates the nexus between Islamic banking products and economic development in Nigeria between 2013Q1 - 2019Q4. The data such as Human Development Index (HDI) proxy of economic development, and Islamic banking products; Murabahah (MUR), Wadiah (WAD), Istisna (IST), and Ijarah (IJA) were gathered from United Nations Statistics and Prudential and Structural Islamic Financial Indicators (PSIFIs). The data were analyzed using Eviews 9. The techniques adopted include descriptive statistics, correlation matrix, unit root test, co-integration statistics and Error Correction Model (ECM). The unit root test showed that all the data series were stationary at the first difference I(1). The co-integration results revealed the existence of a long-run relationship between Islamic banking products and economic development. However, the error correction model established that the short-run disequilibrium would be corrected and signed in the long run at 33%. It was therefore concluded that there exists a nexus between Islamic banking products and economic development in Nigeria. The study recommends among others, that government should encourage more operations of Islamic banking so that Nigeria can achieve the objectives of financial inclusion, which is an essential ingredient of economic development.